Printable Materials for the Realization of High Performance RF Components: Challenges and Opportunities - Eva S. Rosker; Rajinder Sandhu; Jimmy Hester; Mark S. Goorsky; Jesse Tice (International Journal of Antennas and Propagation)
Printing methods such as additive manufacturing (AM) and direct writing (DW) for radio frequency (RF) components including antennas, filters, transmission lines, and interconnects have recently garnered much attention due to the ease of use, efficiency, and low-cost benefits of the AM/DW tools readily available. The quality and performance of these printed components often do not align with their simulated counterparts due to losses associated with the base materials, surface roughness, and print resolution. These drawbacks preclude the community from realizing printed low loss RF components comparable to those fabricated with traditional subtractive manufacturing techniques. This review discusses the challenges facing low loss RF components, which has mostly been material limited by the robustness of the metal and the availability of AM-compatible dielectrics. We summarize the effective printing methods, review ink formulation, and the postprint processing steps necessary for targeted RF properties. We then detail the structure-property relationships critical to obtaining enhanced conductivities necessary for printed RF passive components. Finally, we give examples of demonstrations for various types of printed RF components and provide an outlook on future areas of research that will require multidisciplinary teams from chemists to RF system designers to fully realize the potential for printed RF components.